The effect of translanguaging in teaching the Grade 6 topics of perimeter and area in rural schools. Issue 3 (1st October 2019) - Makonye, Judah Paul
Abstract: The concepts of area and perimeter are problematic to primary and secondary school learners. They often confuse their meaning; often evidenced in assessment tasks by learners misusing the formulae of one for the other. In this research, translanguaging is used as a pedagogical resource to teach these concepts. The study was undertaken on a sample of two Grade 6 classes from two rural Zimbabwean schools. A quasi-experimental research design was used in which there were two experimental and two control groups. The results of the study show that there is a marked difference in performance for learners who used translanguaging over those who used the language of learning and teaching (LoLT) only. Learners developed a strong mathematics register for the concepts of area and perimeter. The errors and misconceptions in the treatment groups were considerably reduced compared to the control groups. The study suggests that translanguaging is beneficial to teaching area and perimeter in particular and overcoming learners' mathematical misconceptions in general.